2021
DOI: 10.3892/mmr.2021.12307
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of ENPP2 by FoxO4 protects cardiomyocytes from doxorubicin‑induced toxicity

Abstract: It has been shown that ferroptosis is involved in doxorubicin (DOX)-induced cardiotoxicity and that ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2) can protect cardiomyocytes from ferroptosis. Thus, the present study aimed to investigate whether ENPP2 could protect cardiomyocytes from DOX-induced injury by inhibiting ferroptosis. H9c2 cardiomyocytes were exposed to various concentrations (0.625, 1.25, 2.5, 5 or 10 µM) of DOX for different time periods. Cell viability and ENPP2 expression were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To this end, first of all, using the PubMed database [ 69 ], we characterized each of the 42 hippocampal DEGs (of tame versus aggressive rats) identified in this work ( Table 2 ), in terms of how downregulation or upregulation of their orthologous human genes can manifest itself in hypertension, as presented [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ,…”
Section: Resultsmentioning
confidence: 99%
“…To this end, first of all, using the PubMed database [ 69 ], we characterized each of the 42 hippocampal DEGs (of tame versus aggressive rats) identified in this work ( Table 2 ), in terms of how downregulation or upregulation of their orthologous human genes can manifest itself in hypertension, as presented [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ,…”
Section: Resultsmentioning
confidence: 99%
“…Under some conditions, it is believed that ferroptosis during MS results in the development of pathogenic T lymphocytes that impair the function of both neuronal and glial cells [296]. Ferroptosis is also involved in tumorigenesis [297] and cardiomyocyte injury as well [298].…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
“…Exercise-induced activation of autophagy results in the down-regulation of FoxO3a and suppression of sarcopenia [232]. Autophagy induction in association with modulation of FoxO signaling also results in decreased renal tubulointerstitial fibrosis [315] and protection against cardiotoxicity during ferroptosis [298].…”
Section: Mammalian Forkhead Transcription Factors and Multiple Sclerosismentioning
confidence: 99%
“…One study suggested that ENPP2 overexpression enhances the expression levels of the ferroptosis-associated gene “GPX4” in H9C2 cells while FoxO4 regulates gene transcription negatively by the suppression of post-transcriptional coding mRNAs. In the H9C2 cells overexpressing ENPP2, DOX-induced increased Fe 2+ activity, ROS and NOX4 production, while decreasing SLC7A11 and reversing GPX4 and FPN expression ( 79 ).…”
Section: Ferroptosis and Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%